2022
DOI: 10.1002/apj.2752
|View full text |Cite
|
Sign up to set email alerts
|

Study on the performance of a novel hydrodynamic cavitation device for treatment of wastewater

Abstract: A novel rotational hydrodynamic cavitation device (called WLAC, composed of rotor and stator) was designed for treatment of wastewater, as well as two other structures with different lead angle based on WLAC, namely, LLAC and HLAC. The velocity characteristics, cavitation number, cavitation bubbles distribution, and production capacity of the hydrodynamic cavitation device were analyzed. Experimental results showed that the concentration of ÁOH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A similar design to Vilarroig's was proposed in the work of Fu and coworkers, with difference that several gaps were also introduced for the stator, presented in Figure 15 [122]. Generation of cavitation bubbles was evaluated by means of CFD study and •OH production measurement for three lead angles: 0 • , 8 • , and 75 • .…”
Section: Axial Serrated Rghcmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar design to Vilarroig's was proposed in the work of Fu and coworkers, with difference that several gaps were also introduced for the stator, presented in Figure 15 [122]. Generation of cavitation bubbles was evaluated by means of CFD study and •OH production measurement for three lead angles: 0 • , 8 • , and 75 • .…”
Section: Axial Serrated Rghcmentioning
confidence: 99%
“…They also reported that cavitation generation decreased with increasing Reynolds number. [122]. Reprinted with permission from Ref.…”
Section: Axial Serrated Rghcmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of studies reporting flow characteristics of this type of devices are Simpson and Ranade , and Abbasi et al Devices based on rotor-stator configuration: It is essential to use either a multiple reference frame or sliding mesh approach for simulating flows in rotor-stator devices. See for example, recent attempts to model cavitating flows in rotor–stators: Sun et al and Fu et al Devices based on swirling flows without any moving parts: Strong swirling flow generated without any moving parts offers additional challenges of potential relaminarization and nonisotropic eddy viscosity to CFD modelers. The advantage of this type of device is that device walls are shielded from collapsing cavities.…”
Section: Current Status Of Modeling Of Hydrodynamic Cavitation Reacto...mentioning
confidence: 99%
“…Devices based on rotor-stator configuration: It is essential to use either a multiple reference frame or sliding mesh approach for simulating flows in rotor-stator devices. See for example, recent attempts to model cavitating flows in rotor–stators: Sun et al and Fu et al…”
Section: Current Status Of Modeling Of Hydrodynamic Cavitation Reacto...mentioning
confidence: 99%